1994
DOI: 10.1111/j.1365-2265.1994.tb02506.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anatomical spectrum in XX sex reversed patients. Relationship to the presence of Y specific DNA‐sequences

Abstract: Although the presence of Y-specific DNA generally results in a more masculinized phenotype, exceptions do occur. In the Y-DNA-negative group, complete or incomplete masculinization in the absence of SRY suggests a mutation of one or more downstream non-Y, testis-determining genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 27 publications
4
75
0
6
Order By: Relevance
“…The majority of these patients have a variable degree of ambiguous external genitalia although a complete male phenotype could also be observed [8,15]. That would be considered as evidence supporting the theory that the SRY gene does not function alone in the determination of the male phenotype, but disruption of an unidentified autosomal or X-linked sex-determining gene may interact in the sex-determining cascade [13,18].…”
Section: Results Of Pcr and Fishmentioning
confidence: 83%
See 2 more Smart Citations
“…The majority of these patients have a variable degree of ambiguous external genitalia although a complete male phenotype could also be observed [8,15]. That would be considered as evidence supporting the theory that the SRY gene does not function alone in the determination of the male phenotype, but disruption of an unidentified autosomal or X-linked sex-determining gene may interact in the sex-determining cascade [13,18].…”
Section: Results Of Pcr and Fishmentioning
confidence: 83%
“…Molecular genetics analyses have demonstrated that approximately 90 % of these patients carry a variable amount of Y material due to a Y-to-X interchange caused by an illegitimate recombination during paternal meiosis [13][14][15]. There was a report of an XX male caused by a translocation of an SRY gene fragment from the Y chromosome to an autosome [16].…”
Section: Results Of Pcr and Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with patients with Klinefelter syndrome, XX males are shorter than normal XY males. This is probably due to the absence of Yq-specific growth gene(s) [9] and to the lack of an appropriate testosterone-dependent pubertal growth spurt [1]. In case 1, however, short stature was observed before puberty.…”
Section: Discussionmentioning
confidence: 76%
“…A large proportion of these males is from Y to X translocations, while others either have no apparent Y;X translocation or have a cryptic sex chromosome mosaicism involving a Y cell line in at least the Sertoli cells [6]. However, XX males present with a spectrum of clinical appearances ranging from phenotypic male individuals to true hermaphrodites [1]. In addition, a population of XX male individuals exists with full or incomplete male phenotype yet no demonstrable SRY gene.…”
mentioning
confidence: 99%